Nutrition for healthy skin strategies for clinical and cosmetic practice - Krutmann, Jean 1959-; Humbert, Philippe 1959- (Springer eBooks., 2011)
This extraordinary reference describes the scientific basis, summarizes the existing evidence that functional food for skin really works, and addresses the key questions asked by dermatologists and patients when it comes to practical aspects of nutrition based strategies in clinical and cosmetical dermatology. It is believed that this helpful guide will become the golden standard, the 'bible' for this given topic, which will be used by dermatologists, industry people and interested patients.